A Review of Surgical Outcomes of Management of Sinonasal Malignancies : A 8-Year of Clinical Experience (2013–2021) at the Tertiary Centre, Sarawak - Leong Wai, Lee; Hanzali, Jumastapha; Tang, Chian Ling; Tang, Ing Ping (Springer Nature Limited, 2024)
Sinonasal carcinoma, a rare and challenging malignancy, originating in the nasal cavity and paranasal sinuses, poses diagnostic and management complexities. This 8-year retrospective analysis at Sarawak General Hospital aims to elucidate demographic trends, histopathological entities, and management outcomes, shedding light on this multifaceted malignancy. Emphasizing the significance of accurate histopathological classification, the study explores the impact on prognostication and treatment strategies. Spanning 2013 to 2021, the study involved 54 patients with sinonasal malignancies. Demographic, clinical, and histopathological details were examined, adhered to the AJCC staging criteria. Analysis involved demographic distributions, tumour characteristics, treatment modalities, and instances of treatment failure. Statistical analysis was done using SPSS version 29.02. The cohort, predominantly male (57.4%) and of Iban ethnicity (44.4%), with a mean age of 52.8 years, exhibited diverse histopathologies, with squamous cell carcinoma as the most common (38.9%). Epistaxis and nasal blockage were common clinical presentations. Advanced stages (III and IV) were prevalent, with the nasal cavity as the primary site. Surgical interventions, mainly endoscopic endonasal excision, were complemented by adjuvant therapies. Complications occurred in 24% of cases. The study highlights a male predilection, occupational risk factors, and a significant association between tobacco smoking and sinonasal cancers. Surgical interventions predominantly utilized the endoscopic approach. Despite a mean survival of 46.6 months, treatment failure occurred in 29.6% of cases, with recurrence and metastasis. Histopathological analysis revealed comparable 5-year disease survival rates between squamous and non-squamous histologies. Treatment failure was significantly associated with the mode of surgery, with open surgery showing a lower incidence. However, nodal status, histopathology types, T staging, and overall staging did display positive associations with treatment failure. This 8-year review provides comprehensive insights into sinonasal carcinoma, addressing demographic, clinical, and histopathological dimensions. The study underlines the complexity of managing this challenging malignancy, emphasizing the need for a holistic approach to patient care. The findings contribute to the understanding of sinonasal carcinoma, guiding clinical decision-making and fostering further research.